Rancang Bangun Sistem Monitoring dan Controlling Suhu Ideal Tanaman Stroberi Berbasis Internet of Things (IoT) - Suhendar, Benny; Fuady, Tb Deddy; Herdian, Yoga (Teknik Informatika Fakultas Ilmu Komputer, 2021)
Monitoring and Controlling the Ideal Temperature of Strawberry Plants Based on the Internet of Thing (IoT) Using Arduino is to realize hardware design, program development, and find out the performance of the tool. Design of Monitoring and Controlling the Ideal Temperature of Strawberry Plants Based on the Internet of Thing (IoT) Using Arduino through 6 stages, namely: problem identification, needs analysis, hardware development, software development, making tools and testing tools. The tool consists of 4 main parts, namely: DHT 11 temperature sensor, Arduino Uno microcontroller, LCD, and RTC. Based on testing the Humidity Temperature Control Tool and Harvesting Monitoring on Arduino Uno-based Strawberry Plant Cultivation, it has functioned as expected. The DHT11 sensor is able to detect the air temperature in a device that is able to move / turn on the fan as a cooler so that the temperature temperature becomes low